Sustainable Fashion MSMEs in Indonesia: How Consumption Value and Green Trust Shape Purchase Intentions - Aida, Imani Nur; Widayati, Catur (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This paper aims to examine how consumption value comprising functional, social, and emotional dimensions, and green trust influence the purchase intention of sustainable fashion products offered by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Methodology/approach – A quantitative survey was conducted among 200 respondents across Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and mediating effects between consumer value dimensions, green trust, and purchase intention. Findings – The results show that functional and emotional values have a significant direct influence on purchase intention, while social value does not. However, green trust plays a significant mediating role in linking all three dimensions of consumer value to purchase intention. Novelty/value – This study emphasizes the importance of green trust in reinforcing the impact of perceived consumer value on purchase intention in the sustainable fashion sector. The findings provide strategic insights for Indonesian MSMEs to craft marketing approaches that strengthen both value perception and environmental credibility, particularly among young and eco-conscious consumers.